Integration of Augmented Reality and Game Technology First Person in the Rukun Hajj Simulation Application with MDLC Method for Introduction Basics About the Rukun of the Hajj Children - Arya Aldi; Tommy; Imran Lubis, (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The pilgrimage (Hajj) is one of the pillars of Islam, consisting of several important stages that need to be understood from an early age. To assist children in learning and understanding the rituals of Hajj interactively, this study develops an application based on Augmented Reality (AR) and First Person Gaming using the Multimedia Development Life Cycle (MDLC) development method. The application aims to provide an enjoyable and educational learning experience through visual simulation and direct interaction with Hajj elements. The use of AR allows children to view and interact with three-dimensional objects of various Hajj rituals in a real-world environment, while the first-person game approach offers a more immersive simulation experience. The results of testing show that the application effectively enhances children's understanding of the Hajj rituals in an engaging and accessible way. This application is expected to serve as an innovative alternative educational medium for introducing the Hajj pillars to younger generations.